Some Results on Wijsman Ideal Convergence in Intuitionistic Fuzzy Metric Spaces. (11th November 2020) - Esi, Ayhan; Khan, Vakeel A.; Ahmad, Mobeen; Alam, Masood
Abstract : In the present work, we study and extend the notion of Wijsman J –convergence and Wijsman J ∗ –convergence for the sequence of closed sets in a more general setting, i.e., in the intuitionistic fuzzy metric spaces (briefly, IFMS). Furthermore, we also examine the concept of Wijsman J ∗ –Cauchy and J –Cauchy sequence in the intuitionistic fuzzy metric space and observe some properties.